(untitled) (Indonesian Sports Justice Review, 2024)
Access to sports and recreational activities is a critical component of social inclusion and individual well-being. This paper examines Indonesia’s sports policies with a focus on inclusivity and equity, highlighting the barriers faced by marginalized groups, including women, people with disabilities, and economically disadvantaged communities. Through policy analysis, case studies, and interviews with stakeholders in Indonesia’s sports sector, the study assesses how national and regional policies promote or hinder equitable access to sports facilities, coaching, and competitions. It explores the role of government and non-governmental organizations in ensuring that sports serve as a tool for social justice, fostering social cohesion and individual empowerment. The paper concludes by proposing a more inclusive sports framework that prioritizes accessibility for all citizens, regardless of gender, socio-economic background, or physical ability, through targeted investment, community-based initiatives, and stronger enforcement of anti-discrimination laws in sports.